Bartke, Wolfgang y Peter Schier. China's New Party Leaderhip. Biographies and Analysis of the Twelfih Central Committee of the Chinese Communist Party. 1985, M.E. Sharpe, Inc, Armonk, New York. 289, pp. - Cornejo Bustamante, Romer (El Colegio de México, 1986)
-